Risk of digestive cancers in a cohort of 69 460 five-year survivors of childhood cancer in Europe: the PanCareSurFup study. Issue 8 (2nd November 2020) - Reulen, Raoul C; Wong, Kwok F; Bright, Chloe J; Winter, David L; Alessi, Daniela; Allodji, Rodrigue M; Bagnasco, Francesca; Bárdi, Edit; Bautz, Andrea; Byrne, Julianne; Feijen, Elizabeth AM; Fidler-Benaoudia, Miranda M; et al.
Abstract : Background: Survivors of childhood cancer are at risk of subsequent primary neoplasms (SPNs), but the risk of developing specific digestive SPNs beyond age 40 years remains uncertain. We investigated risks of specific digestive SPNs within the largest available cohort worldwide. Methods: The PanCareSurFup cohort includes 69 460 five-year survivors of childhood cancer from 12 countries in Europe. Risks of digestive SPNs were quantified using standardised incidence ratios (SIRs), absolute excess risks and cumulative incidence. Results: 427 digestive SPNs (214 colorectal, 62 liver, 48 stomach, 44 pancreas, 59 other) were diagnosed in 413 survivors. Wilms tumour (WT) and Hodgkin lymphoma (HL) survivors were at greatest risk (SIR 12.1; 95% CI 9.6 to 15.1; SIR 7.3; 95% CI 5.9 to 9.0, respectively). The cumulative incidence increased the most steeply with increasing age for WT survivors, reaching 7.4% by age 55% and 9.6% by age 60 years (1.0% expected based on general population rates). Regarding colorectal SPNs, WT and HL survivors were at greatest risk; both seven times that expected. By age 55 years, 2.3% of both WT (95% CI 1.4 to 3.9) and HL (95% CI 1.6 to 3.2) survivors had developed a colorectal SPN—comparable to the risk among members of the general population with at least two first-degree relatives affected. Conclusions: Colonoscopy surveillance before age 55 is recommended in many European countries for individuals with a family history of colorectal cancer, but not for WT and HL survivors despite a comparable risk profile. Clinically, serious consideration should be given to the implementation of colonoscopy surveillance while further evaluation of its benefits, harms and cost-effectiveness in WT and HL survivors is undertaken.